ANALISIS EFISIENSI SALURAN PEMASARAN SAPI POTONG DI KECAMATAN WAELATA KABUPATEN BURU - Muntaviah, Vivin; Matatula, Michel Johan; Tatipikalawan , Jomima M. (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to analyze the marketing channels, marketing margins, and efficiency of beef cattle marketing in Waelata District, Buru Regency. The research employed a survey method with a descriptive quantitative approach through interviews, observations, and documentation. The sample consisted of 32 farmers and 6 traders selected using purposive and snowball sampling techniques. The results identified three marketing channels: Channel I (farmers → consumers), Channel II (farmers → butchers → consumers), and Channel III (farmers → middlemen → butchers → consumers). The margin analysis revealed that longer marketing chains generated higher margins, namely Rp0 in Channel I, Rp1,625,000 in Channel II, and Rp2,168,750 in Channel III. The farmer’s share values were 100%, 82.19%, and 77.75%, respectively, indicating that all channels were still efficient (FS > 50%), although Channel I was the most profitable as farmers received the full selling price without intermediaries. The study concludes that the length of the marketing chain affects the distribution of margins and the share received by farmers, making the choice of marketing channel crucial to maximize profits.